Transfusion-transmissible infections among blood donors in Bejaia, Algeria: ten years retrospective and comparative study - Ferhat Djoudi; Nadir Amir; Mohammed Tahar Chouikh (Journal of Infection in Developing Countries)
Introduction: Blood transfusion saves millions of lives year around the world; it is the most important life-saving option for blood recipients. However, this act is not without risks as contaminated blood may be the source of transfusion-transmissible infections (TTI). This is a retrospective and comparative study on the prevalence of acquired human immunodeficiency syndrome, viral hepatitis B, C and syphilis in blood donors from Bejaia province (Algeria).